The Roundwood Market from the Amazon Forest and the Impacts on the Socio-Economy of the State of Pará - de Santana, Antônio Cordeiro; de Santana, Adamo Lima; Gomes, Sérgio Castro; de Santana, Adina Lima; Costa, Nilson Luiz; de Oliveira, Eder Silva; Bahia, Pablo Queiroz (European Journal of Applied Sciences, 2025)
The objective of this research was to analyze the timber market in five mesoregions of the Amazon forest in the state of Pará, in the period from 2000 to 2013, to determine the influence of deforestation under the market’s regulation and to estimate the monetary value of the timber forest activity. The panel data analysis was applied and the demand and supply equations’s parameters were estimated by the generalized method of moments. The results indicated that the demand and supply of timber are inelastic to the price and significantly influenced by deforestation. The impact of deforestation was positive for demand and higher, in absolute terms, to the negative impact in the supply; resulting in an increment in the market equilibrium price. The socioeconomic and environmental average benefits of timber extraction was US$137.73 million per year by mesoregion, amounting US$688.65 million per year for the state of Pará. From this total, producers appropriated 21.8% and consumers 78.2%. The timber’s equilibrium price was higher than the average prices utilized in forest valuation for the compensations purposes and for the public forest concession projects, indicating an underestimation of the socioeconomic and environmental value of the timber forest capital.